2013
DOI: 10.1111/jssr.12043
|View full text |Cite
|
Sign up to set email alerts
|

Character Strengths and Deep Connections Following Hurricanes Katrina and Rita: Spiritual and Secular Pathways to Resistance Among Volunteers

Abstract: This study investigated a conceptual model with two pathways, altruism and perceived spiritual support, leading to resilience among student volunteers following Hurricanes Katrina and Rita (H‐KR). Both strengths share the sense of deep connections. Parallel pathways with the two major constructs were estimated using structural equation modeling, adjusting for demographics and peritraumatic emotional reactions. The two indicators may have served as a protective mechanism for all volunteers despite differing rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 61 publications
7
48
0
2
Order By: Relevance
“…Our findings are in line with those of Ai et al (2013), who have made the point that perceived spiritual support and altruism are character traits associated with resilience, which they inferred based on low levels of depression symptoms. Consistent with expectations, we found that spiritual support was positively and independently associated with resilience after controlling for the known influences of gender, education, income, prior lifetime trauma, social engagement, and charitable work done for others.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in line with those of Ai et al (2013), who have made the point that perceived spiritual support and altruism are character traits associated with resilience, which they inferred based on low levels of depression symptoms. Consistent with expectations, we found that spiritual support was positively and independently associated with resilience after controlling for the known influences of gender, education, income, prior lifetime trauma, social engagement, and charitable work done for others.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with expectations, we found that spiritual support was positively and independently associated with resilience after controlling for the known influences of gender, education, income, prior lifetime trauma, social engagement, and charitable work done for others. Our findings are in line with those of Ai et al (2013), who have made the point that perceived spiritual support and altruism are character traits associated with resilience, which they inferred based on low levels of depression symptoms. Our findings are generally compatible with this view using a quantitative index of resilience with established psychometric qualities.…”
Section: Discussionsupporting
confidence: 92%
“…Some of the studies focusing on general religious coping (without differentiating between positive and negative coping) showed positive associations between this variable and good psychological functioning: Currier et al ()—positive association with PTG and negative with distress; Hawthorne, Youngblut, and Brooten ()—negative associations with grief, depression, PTSD (only in women), and positive with PTG (only in women); Maschi, Viola, and Morgen ()—positive link with global mental health; Saxon et al (), and negative links with mental disorders (only in women). Nevertheless, no significant links with symptoms of PTSD were demonstrated in a longitudinal study (Bryant‐Davis et al, ; all participants were women); prayer as coping was not linked with symptoms of depression in Ai et al (). Positive links between religious coping and mental disorders were found in Adofoli and Ullman () and Bryant‐Davis, Ullman, Tsong, and Gobin ().…”
Section: Resultsmentioning
confidence: 93%
“…In the pool of studies that assess negative religious coping, the biggest subsection were papers focusing on military trauma. As for the natural disaster trauma , the pattern of relationships is less clear as lack of significant associations among various constructs of religiosity and psychological outcomes was demonstrated in several studies, that is, Chan and Rhodes (), Rosellini et al (), and Ai et al (). However, it has to be noted that the largest subgroup among the studies exploring religious meaning‐making were the papers focusing on natural disasters; all studies in this category yielded significant associations.…”
Section: Resultsmentioning
confidence: 99%
“…This measure was found to be related to enhanced intimate contact with the transcending sacred of the individual's religion. (Ai et al, 2013). Finally, Ai, Tice, Peterson, and Huang (2005) found that faith in prayer was positively correlated with positive emotions and negatively correlated with anxiety.…”
Section: Prayer Duration and Prayer Belief-possible Moderatorsmentioning
confidence: 92%